Construction and testing of decision-problem solving skills test instruments related basic physics content. (April 2020) - Yusal, Y; Suhandi, A; Setiawan, W; Kaniawati, I
Abstract: The aim of this study is to produce test instrument items decision-problem solving skills related to the content of Heat Transfer. The construction of the test instrument has been done using scaffolding which includes stages: description of indicator of decision-problem solving skills, operationalization of indicators, construction of items scenarios, writing of test items, validation of test items, and test of reliability. Validation of test items has been done by five experts namely three education evaluation experts and two physics experts. Test of reliability was carried out by involving 35 students of physics education program at one of the universities in South Sulawesi province. The construction process of the test instrument produced two items of test decision problem solving skills related to the concept of conduction and heat radiation. The results of expert validation of the decision-problem solving test items stated that the constructed items had high validity, and the results of the test reliability showed that the constructed test instruments had a high degree of consistency permanence. These results indicate that the product of decision-problem solving test instrument is worthy of being used for measuring decision-problem solving skills for students of Physics education programs who contract Basic Physics courses.